PERCEPTIONS OF PROSPECTIVE TEACHERS ON BASIC COMPETENCIES IN SCIENCE AT MADRASAH IBTIDAIYAH - Wakhidah, Nur; Erman, Erman; Anugra, Novia (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
Professional teachers have personality competencies, pedagogical, social and professional competencies. One indicator of a professional teacher is if the prospective teacher masters the basic competencies (BC) of the subject being taught. Mastery of BC in the curriculum is very important, so that prospective teachers can plan learning by describing BC into indicators and learning objectives. The depth and breadth of the material available determines the teacher's ability to understand these competencies. Quantitative descriptive research using survey techniques (46 respondents) was conducted to analyze prospective teachers' perceptions of BC which includes cognitive competence and skills competence. The research steps began with preparing a questionnaire in Google Forms (50 Questions) which had been validated by science education experts. Questionnaires were distributed to prospective teachers. Data was analyzed using percentages. The research results showed that prospective madrasa teachers stated that BC skills were more difficult to understand and teach than cognitive BC. The most difficult BC to understand and teach to students in class IV is material about life cycles. In class V, the most difficult are single substances and mixtures. The most challenging material for prospective teachers to understand and teach in class VI is electricity.